Rancang Bangun Aplikasi Stok Opname Berbasis Web - Sutedi, Ade; Fitriani, Leni; Nuraeni, Fitri; Suryani, Isma (Institut Teknologi Garut, 2025)
PT Usaha Garda Arta (UG Arta) Jakarta Branch currently still uses a manual system for cassette stock-taking, which results in the risk of data discrepancies, delays in reporting, and potential recording errors. The operational process begins with the creation of a cash replenishment request by the admin and scheduler to the bank, followed by the collection of cash by the Cash In Transit (CIT) team, sorting by the Cash Processing Center (CPC) team, and finally the replenishment of cash into Automated Teller Machine (ATM) cassettes by the Cash Replenishment (CR) team. This operational process requires team coordination and relies on manual recording, which makes it prone to errors. This research was conducted with the aim of designing a web-based stocktaking system to optimize the cassette stock management process at PT UG Arta's Jakarta Branch. This system is designed with features to input staff and officers, input cassette data, monitor cassette stock, global data and history to improve data accuracy, data recording activities, facilitate monitoring of goods in and out, and reduce manual processes. Therefore, this study is expected to make the stocktaking management process easily accessible to parties involved in the operational process. Additionally, this system is also expected to reduce the risk of recording and reporting errors, thereby improving company performance.